Efficacy of Combined VEGFR1-3, PDGFα/β, and FGFR1-3 Blockade Using Nintedanib for Esophagogastric Cancer - Won, Elizabeth; Basunia, Azfar; Chatila, Walid K; Hechtman, Jaclyn F; Chou, Joanne F; Ku, Geoffrey Y; Chalasani, Sree B; Boyar, Michelle S; Goldberg, Zoe; Desai, Avni M; Tuvy, Yaelle; Berger, Michael F; et al. (Clinical cancer research, 2019)
VEGFR2-directed therapy is commonly used to treat metastatic esophagogastric cancer, but disease progresses in most patients within months. Therapeutic resistance is likely mediated in part by co-occurring amplifications of the genes for multiple oncogenic receptor tyrosine kinases (RTK). We therefore tested the efficacy of combined inhibition of VEGFR1-3, PDGFα/β, and FGFR1-3 using nintedanib. Patients with metastatic esophagogastric adenocarcinoma and disease progression on first-line chemotherapy were treated with nintedanib 200 mg twice daily. The primary endpoint was progression-free survival (PFS) at 6 months; secondary endpoints included tumor response and safety. Tumor biopsies were profiled by targeted capture next-generation sequencing (NGS) to identify molecular predictors of drug response. The study achieved its primary endpoint; 6 of 32 patients (19%) were progression-free at 6 months. With a median follow-up of 14.5 months among survivors, median overall survival (OS) was 14.2 months [95% confidence interval (CI), 10.8 months-NR]. Nintedanib was well tolerated; grade ≥ 3 toxicities were uncommon and included grade 3 hypertension (15%) and liver enzyme elevation (4%). alterations were identified in 18% of patients but were not predictive of clinical outcome on nintedanib therapy. Alterations in cell-cycle pathway genes were associated with worse median PFS (1.61 months for patients with cell-cycle pathway alterations vs. 2.66 months for patients without, = 0.019). Nintedanib treatment resulted in modest disease stabilization in patients with metastatic esophagogastric cancer. Alterations in cell-cycle pathway genes and increased global copy-number alteration (CNA) burden warrant further study as prognostic or predictive biomarkers.